High-Dose Vitamin C Supplementation as a Legitimate Anti-SARS-CoV-2 Prophylaxis in Healthy Subjects—Yes or No? - Gruber-Bzura, Beata M. (Nutrients, 2022)
Vitamin C has a number of acitvities that could contribute to its immune-modulating effects. The only question is whether we should provide ourselves with only the right level of it, or do we need much more during a pandemic? The possibility of reducing the incidence of viral diseases in a well-nourished population through the use of dietary supplements based on vitamin C is not supported in the literature. Despite this, the belief that an extra intake of vitamin C can increase the efficacy of the immune system is still popular and vitamin C is advertised as a remedy to prevent infectious disease. This article refers to the justification of the use of vitamin C in high doses as an anti-SARS-CoV-2 prophylaxis in healthy subjects. Does it make sense or not? As it turns out, any effects of vitamin C supplementation may be more prominent when the baseline vitamin C level is low, for example in physically active persons. People with hypovitaminosis C are more likely to respond to vitamin C administration. No studies regarding prevention of COVID-19 with high-dose vitamin C supplementation in healthy subjects were found.